2023
DOI: 10.1002/eat.23951
|View full text |Cite
|
Sign up to set email alerts
|

Development of transdiagnostic clinical risk prediction models for 12‐month onset and course of eating disorders among adolescents in the community

Abstract: Objective: To develop and internally validate risk prediction models for adolescent onset and persistence of eating disorders. Methods: N = 963 Australian adolescents (11-19 years) in the EveryBODY Study cohort completed online surveys in 2018 and 2019. Models were built to predict 12-month risk of (1) onset, and (2) persistence of a DSM-5 eating disorder. Results: Onset Model. Of the n = 687 adolescents without an eating disorder at baseline, 16.9% were identified with an eating disorder after 12 months. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 71 publications
2
2
0
Order By: Relevance
“…was identified as a core bridge node in the network. Moreover, we found that a symptom of psychological distress (K6-6) was also a bridge node in the network, which is in line with previous research indicating that psychological distress is frequently observed among individuals with EDs (Mitchell et al, 2015;Olguin et al, 2017;Palmieri et al, 2021) and is a high-risk factor for the development of EDs (Brockmeyer et al, 2014;Mitchison et al, 2023;Rasmus et al, 2010).…”
Section: Bridge Nodessupporting
confidence: 91%
See 3 more Smart Citations
“…was identified as a core bridge node in the network. Moreover, we found that a symptom of psychological distress (K6-6) was also a bridge node in the network, which is in line with previous research indicating that psychological distress is frequently observed among individuals with EDs (Mitchell et al, 2015;Olguin et al, 2017;Palmieri et al, 2021) and is a high-risk factor for the development of EDs (Brockmeyer et al, 2014;Mitchison et al, 2023;Rasmus et al, 2010).…”
Section: Bridge Nodessupporting
confidence: 91%
“…Additionally, body dissatisfaction was identified as another central node in the network. This finding aligns with both empirical and conceptual studies highlighting the importance of body dissatisfaction in the development of EDs (Mitchison et al, 2023). For instance, bulimia nervosa has been strongly associated with body dissatisfaction as well as lower self-esteem, more depressive symptoms, and persistent disordered eating attitudes (Laporta-Herrero et al, 2018).…”
Section: Central Nodessupporting
confidence: 87%
See 2 more Smart Citations